Project overview of OPTIMOS-EVE: The fibre-fed multi-object spectrograph for the E-ELT - Navarro, R; Chemla, F; Bonifacio, P; Flores, H; Guinouard, I; Huet, J; Puech, M; Royer, F; Pragt, J; Wulterkens, G; Sawyer, E; Caldwell, M; et al. (2010)
OPTIMOS-EVE (OPTical Infrared Multi Object Spectrograph - Extreme Visual Explorer) is the fibre fed multi object spectrograph proposed for the European Extremely Large Telescope (E-ELT), planned to be operational in 2018 at Cerro Armazones (Chile). It is designed to provide a spectral resolution of 6000, 18000 or 30000, at wavelengths from 370 nm to 1.7 μm, combined with a high multiplex (>200) and a large spectral coverage. Additionally medium and large IFUs are available. The system consists of three main modules: a fibre positioning system, fibres and a spectrograph. The recently finished OPTIMOS-EVE Phase-A study, carried out within the framework of the ESO E-ELT instrumentation studies, has been performed by an international consortium consisting of institutes from France, Netherlands, United Kingdom and Italy. All three main science themes of the E-ELT are covered by this instrument: Planets and Stars; Stars and Galaxies; Galaxies and Cosmology. This paper gives an overview of the OPTIMOS-EVE project, describing the science cases, top level requirements, the overall technical concept and the project management approach. It includes a description of the consortium, highlights of the science drivers and resulting science requirements, an overview of the instrument design and telescope interfaces, the operational concept, expected performance, work breakdown and management structure for the construction of the instrument, cost and schedule. © 2010 Copyright SPIE - The International Society for Optical Engineering.